SESN2 maintains cartilage homeostasis by SREBP1-mediated lipid metabolism during osteoarthritis progression - Zizheng Liu; Huiming Jiang; Zhaofeng Zhang; Ruiyang Jiang; Rongliang Wang; Jiawei Li; Weitong Li; Guihua Tan; Yuxiang Fei; Zhongyang Lv; Hu Guo; Ziyin Sun; et al. (iScience)
Summary: Chondrocytes experience adverse lipid metabolism disorders during the degeneration of cartilage in osteoarthritis (OA), while the underlying mechanisms remain poorly understood. Sestrin2 (SESN2), a highly conserved stress-inducible protein, plays a crucial role in regulating lipid metabolism. This study aimed to investigate the role of SESN2 in the regulation of fatty acid metabolism in chondrocytes and elucidate the underlying molecular mechanisms in OA. The expression of SESN2 was significantly decreased in OA-affected human cartilage, and this decrease correlated with the upregulation of lipogenic enzymes. Sesn2 inhibited lipogenic enzyme expression in chondrocytes and improved cartilage homeostasis. Mechanistically, SESN2 inhibited the expression of sterol regulatory element-binding transcription factor 1 (SREBP1) and interacted with SREBP cleavage-activating protein (SCAP) to deactivate SREBP1-mediated transcription for lipogenesis. Finally, overexpression of Sesn2 in mice undergoing destabilization of medial meniscus (DMM) surgery ameliorated OA pathological manifestations and improved behavioral experiment performance through inhibiting fatty acid synthesis. Our findings revealed that SESN2 suppresses SREBP1-mediated transcription of lipogenic enzymes in chondrocytes and ameliorates OA progression. These results highlighted that targeting SESN2 may serve as a promising therapeutic strategy for OA.